Characterization of intermediate stages in the precipitation of hydroxyapatite at 37 degrees C - Filipa Castro (2012)
Precipitation of hydroxyapatite Ca-5(PO4)(3)OH (HAp) was carried out by mixing a saturated calcium hydroxide aqueous solution with an orthophosphoric acid aqueous solution at 37 degrees C. In order to promote optimal conditions for the production of HAp with high yields, mixing of the reaction medium was assured by a novel metal stirrer. Different experimental conditions were studied varying the mixing Ca/P molar ratio from 1 to 1.67. After process optimization, a suspension of HAp particles with pH close to 7 was obtained for a mixing molar ratio Ca/P=1.33. The precipitation process was then characterized as a function of pH and calcium concentration, revealing the existence of three different stages. The precipitate formed in each stage was characterized by scanning electron microscopy and X-ray diffraction.